Biomedical engineering : bridging medicine and technology - Saltzman, W. Mark, 1959- (Cambridge texts in biomedical engineering, 2015)
"The second edition of this popular introductory undergraduate textbook uses examples, applications, and profiles of biomedical engineers to show students the relevance of the theory and how it can be used to solve real problems in human medicine. The essential molecular biology, cellular biology, and human physiology background is included for students to understand the context in which biomedical engineers work. Updates throughout highlight important advances made over recent years, including iPS cells, microRNA, nanomedicine, imaging technology, biosensors, and drug delivery systems, giving students a modern description of the various subfields of biomedical engineering. Over 200 quantitative and qualitative exercises, many new to this edition, help consolidate learning, whilst a solutions manual, password-protected for instructors, is available online. Finally, students can enjoy an expanded set of leader profiles in biomedical engineering within the book, showcasing the broad range of career paths open to students who make biomedical engineering their calling"--Resumé vydavatele